Intermittent fasting and time-restricted eating role in dietary interventions and precision nutrition - Ghada A. Soliman (Frontiers Media S.A., 2022)
Intermittent fasting (IF), time-restricted eating (TRE) and fasting-mimicking diets (FMD) are gaining popularity as weight loss programs. As such, the timing and frequency of meals have been recognized as essential contributors to improving cardiometabolic health and a role as adjuvant therapy in cancer. Randomized controlled trials suggested that the weight loss associated with IF is due to a reduced energy intake due to time restriction. Although the supervised TRE clinical trials documented the dietary caloric intake, many free-living studies focused on the timing of meals without a complete characterization of the dietary intake, caloric density, or macronutrient composition. It is possible that both caloric-restriction diets and time-restriction protocols could work synergistically or additively to improve metabolic health outcomes. Like personalized medicine, achieving precision nutrition mandates the provision of the right nutrients to the right patient at the right time. To accomplish this goal, future studies need to evaluate the benefits of IF and TRE. Randomized controlled trials were conducted in different populations, ethnic groups, ages, geographic distribution, physical activity levels, body composition and in patients with obesity, diabetes, and cardiovascular diseases. Also, it is crucial to analyze the dietary composition and caloric density as related to circadian rhythm and timing of meals. It is conceivable that IF and TRE may contribute to precision nutrition strategies to achieve optimal health. However, more research is needed to evaluate IF and TRE effects on health outcomes and any side effects.